Midkine in Inflammation. (27th December 2011) - Weckbach, Ludwig T.; Muramatsu, Takashi; Walzog, Barbara
Abstract : The 13 kDa heparin-binding growth factor midkine (MK) was originally identified as a molecule involved in the orchestration of embryonic development. Recent studies provided evidence for a new role of MK in acute and chronic inflammatory processes. Accordingly, several inflammatory diseases including nephritis, arthritis, atherosclerosis, colitis, and autoimmune encephalitis have been shown to be alleviated in the absence of MK in animal models. Reduced leukocyte recruitment to the sites of inflammation was found to be one important mechanism attenuating chronic inflammation when MK was absent. Furthermore, MK was found to modulate expression of proinflammatory cytokines and the expansion of regulatory T-cells. Here, we review the current understanding of the role of MK in different inflammatory disorders and summarize the knowledge of MK biology.